2016
DOI: 10.14203/reinwardtia.v14i2.1678
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Rafflesia (Rafflesiaceae) in Sumatra With a New Record Rafflesia Gadutensis Meijer

Abstract: MAHYUNI, R., KUSUMA,Y. W. C., WIHERMANTO & VELDKAMP, J. F. 2015. Notes on Rafflesia (Rafflesiaceae) in Sumatra with a new record Rafflesia gadutensis Meijer. Reinwardtia 14(2): 317 - 322. Pulau Mursala is a small island west of the Sibolga, Tapanuli Tengah District, North Sumatra, Indonesia. The occurrence of the genus Rafflesia (Rafflesiaceae) there has never been reported before. However, during a visit in April 2013 three populations are located close together with more than twenty buds and some rotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…Hence, we interpreted that Meijer's statement likely referred to the location at the boundary between the perigone tube and diaphragm and not to the upper part of the perigone tube. Our interpretation is matched by the illustration in Mahyuni et al (2015) showing branched ramenta, not toadstool, on the upper part of the perigone tube. Susatya et al (2017) also found compound toadstool ramenta only in the lower part of the diaphragm.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Hence, we interpreted that Meijer's statement likely referred to the location at the boundary between the perigone tube and diaphragm and not to the upper part of the perigone tube. Our interpretation is matched by the illustration in Mahyuni et al (2015) showing branched ramenta, not toadstool, on the upper part of the perigone tube. Susatya et al (2017) also found compound toadstool ramenta only in the lower part of the diaphragm.…”
Section: Discussionsupporting
confidence: 81%
“…Key differences between R. kemumu and R. gadutensis are color of the perigone lobes; pattern, size, number, and color of warts on the upper surface of the perigone lobes; color and wart presence/absence on the upper surface of the diaphragm; blot arrangement of the two concentric rings of the windows closest to the diaphragm opening; types and distribution of ramenta; number and shapes of processes; and number of anthers (Table 1). Meijer (1984Meijer ( , 1997, Mahyuni et al (2015), and Susatya et al (2017) or obtained from photos by the late Prof.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations